IMPLEMENTASI DATA MINING UNTUK MENDUKUNG SISTEM MANAJEMEN PERKERASAN JALAN DI INDONESIA - Rifai, A. Irfan; Pereira, Paulo; Hadiwardoyo, Sigit P.; Correia, A. Gomes; Cortez, Paulo (Jurnal HPJI, 2015)
Abstract The use of service level indicators of road surface by using the International Roughness Index (IRI) has been widely used in many countries including Indonesia. Pavement Management System was developed in Indonesia by using the data IRI. The increasing of roads network and limitations of the tool to measure the road surface (roughness meters), so the number of the recording can not fully recorded. But recording the performance data of the road network has been widely performed manually. This data has been collected in a basis data so that these can be used to create a model for IRI through data mining approaches. The extraction of data from the national road network to the region of West Java is used as a case study in the study. IRI data mining models have been developed in this study with the approach of Artificial Neural Network and Support Vector Machines. The results of the IRI model development approach is validated by the level of 90 %. The success of the development of this model can be used to use the existing data to support the management of the road network with the Pavement Management System. Keywords: road surface, pavement management, data mining, IRI model Abstrak Penggunaan indikator tingkat layanan permukaan jalan dengan International Roughness Index (IRI) sudah banyak digunakan di berbagai negara termasuk di Indonesia. Bahkan Sistem Manajemen Perkerasan di Indonesia dikembangkan dengan menggunakan data IRI. Namun luasnya jaringan jalan dan keterbatasan alat ukur untuk menilai kerataan permukaan jalan menyebabkan pencatatan tingkat layanan jalan masih belum menyeluruh. Meskipun demikian data kinerja jaringan jalan yang dilakukan secara manual telah banyak dilakukan. Hasil pencatatan data yang lengkap ini sudah berbentuk basis data yang diharapkan dapat dimanfaatkan untuk menyusun model IRI melalui pendekatan data mining. Model IRI dengan data mining yang dikembangkan pada studi ini menggunakan pendekatan Artificial Neural Network dan Support Vector Machines. Hasil pengembangan model IRI ini divalidasi dengan tingkat kesesuaian 90 %. Hasil pengembangan model ini dapat digunakan untuk memanfaatkan data yang ada untuk mendukung pengelolaan jaringan jalan dengan Sistem Manajemen Perkerasan. Kata-kata kunci: permukaan jalan, manajemen perkerasan, data mining, model IRI